Tom Peters - Heller, Robert (DK business masterminds., 2000)
The world's most innovative management guru and co-author of "In Search of Excellence", Tom Peters is the leading advocate of management by "perpetual revolution", showing businesses how to survive and succeed in an upside-down world. In this volume, Robert Heller reveals the full range of Tom Peters's extraordinary management vision and presents a series of masterclasses that show how to practice the theories of the management messiah.